Anxiety associated with palatable food withdrawal is reversed by the selective FAAH inhibitor PF-3845: A regional analysis of the contribution of endocannabinoid signaling machinery - De Ceglia, Marialuisa; Micioni Di Bonaventura, Maria Vittoria; Romano, Adele; Friuli, Marzia; Micioni Di Bonaventura, Emanuela; Gavito, Ana L.; Botticelli, Luca; Gaetani, Silvana; Rodriguez-de-Fonseca, Fernando; Cifani, Carlo (Wiley, 2023)
Objective: Consumption of energy-dense palatable "comfort" food can alleviate stress and negative emotions, while abrupt withdrawal from a palatable diet can worsen these symptoms, causing difficulties with adherence to weight-loss diets. Currently, no pharmacological treatment is effective for obesity-related anxiety, so we investigated the endocannabinoid system (ECS), and specifically the fatty acid amide hydrolase (FAAH), as an interesting emerging target in this context because of its key role in the regulation of both energy homeostasis and emotional behavior. Methods: Rats were subjected to exposure and subsequent abstinence from a palatable cafeteria diet. During abstinence period, rats were treated with the selective FAAH inhibitor PF-3845 (10 mg/kg; intraperitoneal administration every other day). Results: Abstinent rats displayed an anxiogenic-like behavior and changes in the proteins of ECS signaling machinery in brain areas involved both in anxiety and food intake regulation. In particular, withdrawal caused a reduction of the expression of cannabinoid receptors in the nucleus accumbens and of enzymes diacylglycerol lipase alpha and monoacylglycerol lipase (MAGL) in the amygdala. Pharmacological inhibition of FAAH exerted an anxiolytic-like effect in abstinent animals and increased both MAGL expression in amygdala and CB2 expression in prefrontal cortex. Discussion: Overall, our results suggest that emotional disturbances associated with dieting are coupled with region-specific alterations in the cerebral expression of the ECS and that the enhancement of the endocannabinoid signaling by FAAH inhibition might represent a novel pharmacological strategy for the treatment of anxiety related to abstinence from palatable food.
Keywords: Estrés (fisiología); Hábitos alimenticios - Aspectos psicológicos; Abstinence; Anxiety; Endocannabinoid system; Fatty acid amide hydrolase; Obesity; Palatable diet; PF-3845